Intensive Safety Monitoring of Rituximab (Biosimilar Novex® and the Innovator) in Pediatric Patients With Complex Diseases - Riva, Natalia; Molina, Manuel; Cornaló, Berta L.; Salvador, María V.; Savransky, Andrea; Tenembaum, Silvia; Katsicas, María M.; Monteverde, Marta; Cáceres Guido, Paulo; Rousseau, Marcela; Staciuk, Raquel; González Correas, Agustín; et al. (Frontiers in Pharmacology, 2022)
Although rituximab is widely used off-label for complex pediatric diseases, safety reports are limited. We aimed to report evidence of its use in clinical practice, to describe the incidence of adverse drug reactions (ADR) to rituximab biosimilar Novex® and innovator, and to identify risk factors for the development of ADR in a real-life follow-up cohort of pediatric patients with complex diseases. We conducted a prospective, longitudinal, observational, single-centre study in patients that received rituximab for any complex disease, as part of an intensive pharmacovigilance program. Demographic, pharmacological, clinical, and drug-related data were collected for all patients. ADR-free survival, including infusion-related reactions (IRR) and delayed ADR (dADR), was estimated using Kaplan-Meier curves. Risk factors were evaluated by multivariable Cox regression models. In total, 77 patients ( < 19 y.o.) received 187 infusions of rituximab Novex® (n=155) or innovator rituximab (n=32) for neurologic (Neu), immune-hematologic-rheumatic (IHR), oncologic (O) diseases, hematopoietic stem-cell transplantation (HSCT) or solid organ transplantation (SOT). We recorded 29 IRR and 58 dADR that occurred in 27 (35.1%) and 29 (37.7%) patients, respectively. The respiratory tract was the most affected during IRR (29.6%) and hypogammaglobulinemia (37.9 %) was the most frequent dADR. First versus subsequent infusions (HR 5.4, CI95% 2.4-12.1, p˂0.05), sex (boys vs girls, HR 0.3, CI95% 0.1-0.8, p˂0.05), and diagnosis (Neu-IHR diseases vs O-HSCT-SOT, HR 2.3, CI95% 1.02-5.4, p<0.05) were significantly associated with the development of IRR. For dADR, risk factors were diagnosis (Neu-IHR diseases vs O-HSCT-SOT, HR 0.4, CI95% 0.2–0.9, p<0.05) and cumulative body surface area-normalized dosage (HR 1.0003, CI95% 1.0001–1.0006, p<0.05). The present is the largest real-world safety assessment of rituximab in Latin-American children with complex diseases supporting its use based on the overall acceptable safety. Identification of risk factors may contribute to optimization of off-label rituximab treatment in pediatrics.